Immunological configuration of ovarian carcinoma: features and impact on disease outcome - David Cibula; Ignace Vergote; An Coosemans; Lorenzo Galluzzi; Radek Špíšek; Jitka Fucikova; Sandra Orsulic (Journal for ImmunoTherapy of Cancer)
Epithelial ovarian carcinoma (EOC) is a relatively rare malignancy but is the fifth-leading cause of cancer-related death in women, largely reflecting early, prediagnosis dissemination of malignant disease to the peritoneum. At odds with other neoplasms, EOC is virtually insensitive to immune checkpoint inhibitors, correlating with a tumor microenvironment that exhibits poor infiltration by immune cells and active immunosuppression. Here, we comparatively summarize the humoral and cellular features of primary and metastatic EOC, comparatively analyze their impact on disease outcome, and propose measures to alter them in support of treatment sensitivity and superior patient survival.